THE EFFECT OF SERVICE QUALITY AND PRICE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION ON LAUNDRY MEDAN.COM THE CITY OF MEDAN - Hazmanan Khair; Satria Tirtayasa; Muhammad Yusron (Jurnal Ekonomi, 2023)
The purpose of this study was to examine and analyze the effect of service quality and price on customer loyalty through customer satisfaction directly or indirectly. The approach used in this study is a causal approach. The population in this study is all customers Laundry Medan.Com. the sample in this study using the formula Slovin amounted to 286 customers Laundry Medan.Com. data collection techniques in this study using documentation techniques, observation, and questionnaires. Data analysis techniques in this study using a quantitative approach using statistical analysis by using the Auter Model Analysis Test, Inner Model Analysis, and hypothesis testing. Data processing in this study using software program PLS (Partial Least Square). The results of this study indicate that the quality of service, price and customer satisfaction have a significant effect on customer loyalty and service quality and price have a significant effect on customer satisfaction, and indirectly the quality of Service and price have a significant effect on customer loaylitas through consumer satisfaction in Laundry Medan.Com